Marker-assisted selection for rice brown planthopper (Nilaparvata lugens)resistance using linked SSR markers - Shabanimofrad, Mahmoodreza; Yusop, Mohd Rafii; Ashkani, Sadegh; Musa, Mohamed Hanafi; Adam, Nur Azura; Iffah Haifa,; Harun, Abdul Rahim; Abdul Latif, Mohammad (Scientific and Technical Research Council of Turkey, 2014)
Developing cultivars resistant against different biotypes of brown planthopper (BPH) through marker-assisted selection (MAS) is an effective management strategy to control this pest. In this study, 28 polymorphic simple sequence repeat (SSR) markers were analyzed in 108 F3 progenies derived from the cross of Rathu Heenati and MR276 rice cultivars to investigate the association with BPH resistance against biotypes 2 and 3. For statistical analysis, parents and their offspring were grouped into 2 phenotypic classes based on their levels of BPH resistance. Chi-square analysis demonstrated a good fit to a ratio of 3:1 for the segregation of resistance and susceptibility. Association of SSR markers with phenotypic traits in F3 progenies were identified. Six SSR markers (RM401, RM5953, RM217, RM210, RM242, and RM1103) were significantly associated with BPH resistance to biotypes 2 and 3 of BPH. Out of these 6 markers, RM401, RM5953, and RM217 accounted for about 17% of total phenotypic variation and RM210, RM242, and RM1103 accounted for 20% of total phenotypic variation against biotypes 2 and 3, respectively. Therefore, the above 6 markers were confirmed for MAS in rice breeding programs to develop BPH-resistant rice cultivars.